ЗА ПРАВИЛЬНОЕ РЕШЕНИЕ, ЕЩЁ ПО 15 ПКТ. №1.7-3(х-1)=2х №2.6(2х+0,5)=8х-(3х+4) №3.10-х(5-(6+х))=х(х+3)-4х №4.5х-2(х-3)=6х №5.6х-(2х+5)=2(3х-6) №6.х(х(х-1))+6=х(х+3)(х-4) №7.6-4(х+1)=3х №83(х-2)=7+(2х-5)
ЗА ПРАВИЛЬНОЕ РЕШЕНИЕ, ЕЩЁ ПО 15 ПКТ.
№1.
7-3(х-1)=2х
№2.
6(2х+0,5)=8х-(3х+4)
№3.
10-х(5-(6+х))=х(х+3)-4х
№4.
5х-2(х-3)=6х
№5.
6х-(2х+5)=2(3х-6)
№6.
х(х(х-1))+6=х(х+3)(х-4)
№7.
6-4(х+1)=3х
№8
3(х-2)=7+(2х-5)
Ответ(ы) на вопрос:
Гость
1) 7 - 3x - 3 = 2x 4 = 5X X = 4\5 ////////////////////////////// 2) 12X + 3 = 8x - 3x - 4 12x - 8x + 3x = - 4 - 3 7x = - 7 x = - 1 /////////////////////////////// 3) 10 - X( 5 - 6 - x) = x^2 + 3x - 4x 10 - 5x + 6X +x^2 = x^2 - x 10 + x +x^2 = x^2 - x 10 = - x - x^2 + x^2 - x 10 = - 2x x = - 5 ///////////////////////////////// 4) 5x - 2x + 6 = 6X 3x - 6x = - 6 - 3x = - 6 x = 2 ////////////////////////////////////////////// 5) 6x - 2x - 5 = 6x - 12 4x - 6x = - 12 + 5 - 2x = - 7 x = 7/2 = 3.5 ///////////////////////////////////////// 6) x(x^2 - x) + 6 = (x^2 + 3x)(x - 4) x^3 - x^2 + 6 = x^3 - 4x^2 + 3x^2 - 12x x^3 - x^2 - x^3 + x^2 + 12x = - 6 12x = - 6 x = - 0,5 //////////////////////////////////////////// 7) 6 - 4x - 4 = 3x - 4x - 3x = - 6 + 4 - 7x = - 2 x = 2\7 //////////////////////////////////////////// 8) 3x - 6 = 7 + 2x - 5 3x - 2x = 6 + 7 - 5 x = 8 //////////////////////////////////////////
Не нашли ответ?
Похожие вопросы